KEMAMPUAN MENULIS PARAGRAF PERSUASI SISWA KELAS X SMAN 9 PADANG DENGAN MENGGUNAKAN MEDIA IKLAN PRODUK - Yuhendri, April; Nisja, Indriani; Muhardis, Muhardis (Pendidikan Bahasa Indonesia, 2013)
The background of this research because the studentâs ability in writing persuasive paragraph is lower. The goal of this research is to describeÂ the ability of the first year students in writing persuasive paragraph by using product advertisement media.The theoretical foundations which are used in this research,as follows : The definition of writing,Â Kinds of paragraph and defenition of persuasive paragraph that according to Atmazaki.Â Kind of the research is the quantitative research by using descriptive method.The population in this research is the first year students of SMAN 9 Padang who had registered in academic 2012/2013. The sample of this research is the first year students of SMAN 9 Padang who choosed by random sampling and total sample are 39 students. The data of this research was score of students ability In writing persuasive paragraph at the first year students of SMAN 9 Padang by using product advertisement media.Â The goal of this research, as follow : First, the ability of the first year students at SMAN 9 Padang in writing persuasive paragraph by using product advertisement media for data indicator and fact that appropriate with media is more than Enough ( mean 71,15). Second, the ability of the first year students at SMAN 9 Padang in writing persuasive paragraph by using product advertisement media for persuade indicator is Good ( mean 76 ). Third, the ability of the first year students at SMAN 9 Padang in writing persuasive paragraph by using product advertisement media for logic sentence indicator is Very Good ( mean 85,25). Fourth, the ability of the first year students at SMAN 9 Padang in writing persuasive paragraph by using product advertisement media for validity sentence indicator is Enough ( mean 62,17). Based on the conclution from those four indicators we concluded that the ability of the first year students at SMAN 9 Padang in writing persuasive paragraph by using product advertisement media belong to more than Enough ( mean 73,55).